2013
DOI: 10.1002/cjce.21853
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and flow characteristics of nanofluid in a narrow annulus: Numerical study, modelling and optimisation

Abstract: This study attempts to evaluate the flow and heat transfer characteristics of water–Al2O3 nanofluid in a narrow annulus. The effects of volume fraction, the size of particles and the ratio of inner wall heat flux to outer wall heat flux were investigated on the convective heat transfer coefficients and friction coefficients at inner and outer walls of the annulus. Using smaller particles caused a greater heat transfer coefficient. Meanwhile, at higher volume fractions, changing the size of particles led to mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Heat Transfer and Flow Characteristics of Nanofluid in a Narrow Annulus: Numerical Study, Modelling and Optimisation [11] [p. 747]…”
Section: Enumerativementioning
confidence: 99%
“…Heat Transfer and Flow Characteristics of Nanofluid in a Narrow Annulus: Numerical Study, Modelling and Optimisation [11] [p. 747]…”
Section: Enumerativementioning
confidence: 99%
“…[ 12,13 ] As a new type of working material, nanofluids have been widely applied in microchannels, [ 14 ] photothermal conversion, [ 15 ] as well as heat exchangers. [ 16,17 ] In recent years, TiO 2 nanofluids have become a research hotspot because they can efficiently enhance the thermal conductivity of fluids and have better dispersion stability than other metal oxide nanofluids. [ 18 ] To date, the study of TiO 2 in heat exchange systems has primarily concentrated on the influence of mass fraction of nanoparticles on thermal transfer properties and stability of nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Many research reported a significant progress achieved when dealing with the coaxial free jets, which improves the region of the potential core and the turbulence intensity at the nozzle outlet due to the presence of mixing of the primary and secondary streams. Coaxial flows are used in novel domains for instance in the non-Newtonian nanofluid in heat exchangers (Bahiraei et al 2014, Bahiraei 2016, Bahiraei et al (2017a, 2017b).…”
Section: Introductionmentioning
confidence: 99%